Effect of Nitrogen and Variety on Agronomic Performance of Rhodes Grass (Chloris gayana Kunth) in the Sudan (Global Journal of Science Frontier Research, 2020)
An experiment was conducted in Shambat (2016)(2017) in the demonstration farm of the College of Agricultural Studies, Sudan University for Science and Technology, to study the effect of variety and nitrogen fertilization on the agronomic performance of Rhodes grass. Two Rhodess grass varieties (Fine cut and Reclaimer) and 2 nitrogen doses plus control were studied across seven cuts. The treatments were replicated four times in split plot experiment with fertilizer doses assigned to the main plots and the varieties to the sub-plots. The data collected included forage yield, plant height and days to 50% flowering.
Keywords: fine cut; reclaimer; tetraploid; diploid